Molecular Genetics, Clinical Characteristics, and Treatment Outcomes of KATP-Channel Neonatal Diabetes Mellitus in Vietnam National Children’s Hospital - Ngoc, Can Thi Bich; Dien, Tran Minh; De Franco, Elisa; Ellard, Sian; Houghton, Jayne A. L.; Lan, Nguyen Ngoc; Thao, Bui Phuong; Khanh, Nguyen Ngoc; Flanagan, Sarah E.; Craig, Maria E.; Dung, Vu Chi (Frontiers in Endocrinology, 2021)
Neonatal diabetes mellitus (NDM) is defined as insulin-requiring persistent hyperglycemia occurring within the first 6 months of life, which can result from mutations in at least 25 different genes. Activating heterozygous mutations in KCNJ11 or ABCC8 genes are the most common cause of NDM. Patients with NDM caused by KATP channel mutations are sensitive to sulfonylurea (SU) treatment; Patients and methods: Seventy patients were diagnosed with NDM at Vietnam National Children’s Hospital and molecular genetic testing for all genes known to cause NDM was performed at the Exeter genomic laboratory, UK. Patients with ABCC8 or KCNJ11 mutations were transferred from insulin to oral SU. Clinical characteristics, molecular genetics and annual data relating to glycemic control, SU dose, severe hypoglycemia and side-effects were collected. The main outcomes of interest were SU dose, SU failure, and glycemic control (HbA1c). Results: Fifty-four of 70 patients (77%) with NDM harbored a genetic mutation and of these, 27 (50%) had mutations in ABCC8 or KCNJ11. A total of 21 pathogenic mutations were identified in these patients (13 mutations in ABCC8 and 8 mutations in KCNJ11). Overall, 51% had low birth weight (below 3rd percentile), 23 (85%) were diagnosed before 3 months of age and 23 (85%) presented with diabetic ketoacidosis. At diagnosis, clinical and biochemical findings (mean ± SD) were pH 7.16 ± 0.16, HCO3- 7.9 ± 7.4 mmol/L, BE -17.9 ± 9.1 mmol/L, HbA1C 7.98 ± 2.93 %, blood glucose 36.2 ± 12.3 mmol/L, and C-peptide median 0.09 (range 0 - 1.61 nmol/l). Twenty-six patients were successfully transferred from insulin to SU therapy. In the remaining case, remission of diabetes occurred prior to transfer. Glycemic control on SU treatment was better than on insulin treatment: HbA1c and blood glucose level decreased from 7.58 ± 4.63% and 19.04 ±14.09 mmol/L when treated with insulin to 5.8 ± 0.94% and 6.87 ± 3.46 mmol/L when treated with SU, respectively. Conclusions: This is the first case series of NDM patients with ABCC8/KCNJ11 mutations reported in Vietnam. SU is safe in the short term for these patients. It is important to perform gene mutations for patients with NDM.